Disseminating climate information services using digital platforms in Mali - Diallo, Aboubacar; Bengaly, Oumar; Dossou-Yovo, Elliott (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Mali agriculture remains highly vulnerable to the impacts of climate variability, particularly for smallholder rice farmers facing unpredictable rainfall, droughts, and rising temperatures. To address these challenges, the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project in Mali developed and scaled digital platforms to deliver personalized, location-specific climate information services (CIS). This farmer-centered platform, integrating tools such as WhatsApp, phone calls, SMS, and radio broadcasts provided actionable forecasts and agro-climatic advisories tailored to farmers’ specific needs and locations. Between January and June 2025, 427,155 rice farmers (41% women) accessed CIS through these platforms. USe of CIS enabled significant improvements in agricultural outcomes, with rice yields increasing by 1,600 kg/ha, incomes rising by 561 USD/ha, and food consumption scores improving by 11 points. The interactive, inclusive design of the digital platform not only enhanced farmers' adaptive capacity but also demonstrated a scalable model for climate-resilient agricultural development in Mali’s rice-based systems.